Negotiation of Meaning and Form Processes in Student-Teacher Communication - Indriyani, Christina Eli; Xenia, Tia; Kusuma, Paulina Chandrasari (Universitas Pahlawan Tuanku Tambusai, 2025)
The process of negotiating meaning and form can contribute to successful communication and become an attempt of the interlocutors to overcome comprehension difficulties when the communication is interrupted. The present research explores the interactional nature of teacher-student communication during English classrooms. Analyzing the process of negotiation relatively serves as a major basis in this study; however, the extended process needs to be seen as the negotiation reaches mutual understanding. This study, therefore, aims to identify whether the negotiation of meaning and form reach the resolution and mutual interchangeability, and investigate the structures. The data were 20 teaching practicum videos of 10 student-teachers. Mixed method research was employed in this study. The quantitative and qualitative analysis were used to find out the number of negotiations that reached resolution and the structure of negotiation process respectively. The results showed 70% of interactional work between teacher and students in the negotiation processes, for both meaning and form, achieves mutual interchangeability with variety of negotiation route. Variations of its structure are made as strategies of successful communication for teacher candidates to acquire. Eventually, this study provides theoretical and practical benefits for the student-teachers, the lecturers, and the English Education Department.